Exploring Apology Strategy by Indonesian Public Figures: A Pragmatic Study in Social Media - Budi Abudin; Hanna Sundari (Deiksis, 2021)
Public figures tend to use social media platforms to apologize in public due to its practicality and effectiveness. Although public apology as a social phenomenon has been extensively studied in the English-speaking world, Indonesian public apologies have less attention from linguists and management scientists. This paper examines the speech act of apologizing made by Indonesian Public Figures in 2020 by analyzing videos collected from YouTube. The data of the study was analyzed based on Murphy’s framework of formulate (2015). Findings include that Indonesian public figures prefer all three categories of apology strategy: explicit, conventional-indirect, and non-conventional-indirect strategies. Mover, explanation, account, or excuse become the most frequent used to express their apology. It was then followed by expression of lack of intent and statement of repair. Keywords: Pragmatic, Apology, Indonesia, Youtube, Public Figures